The Value of Prognostic Nutritional Index (PNI) on Newly Diagnosed Diffuse Large B-Cell Lymphoma Patients: A Multicenter Retrospective Study of HHLWG Based on Propensity Score Matched Analysis - Shen Z; Wang F; He C; Li D; Nie S; Bian Z; Yao M; Xue Y; Wang Y; Gu W; Zhu T; Shi Y; et al. (Dove Medical Press, 2021)
Ziyuan Shen,1,* Fei Wang,2,* Chenlu He,1,* Dashan Li,3 Shanlin Nie,3 Zhenzhen Bian,3 Mingkang Yao,4 Yuhao Xue,5 Ying Wang,6 Weiying Gu,2 Taigang Zhu,7 Yuye Shi,5 Hao Zhang,4 Shuiping Huang,1,8 Yuqing Miao,9 Wei Sang3 On behalf of the Huaihai Lymphoma Working Group1Department of Epidemiology and Biostatistics, Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China; 2Department of Hematology, The First People's Hospital of Changzhou, Changzhou, Jiangsu, People's Republic of China; 3Department of Hematology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China; 4Department of Hematology, Affiliated Hospital of Jining Medical University, Jining, Shandong, People's Republic of China; 5Department of Hematology, The First People's Hospital of Huaian, Huaian, Jiangsu, People's Republic of China; 6Department of Personnel, Suqian First Hospital, Suqian, Jiangsu, People's Republic of China; 7Department of Hematology, The General Hospital of Wanbei Coal-Electric Group, Suzhou, People's Republic of China; 8Center for Medical Statistics and Data Analysis, Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of China; 9Department of Hematology, Yancheng First People's Hospital, Yancheng, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei SangDepartment of Hematology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People's Republic of ChinaTel +8613645207648Email xyfylbl515@xzhmu.edu.cnYuqing MiaoDepartment of Hematology, Yancheng First People's Hospital, Yancheng, Jiangsu, People's Republic of ChinaTel +8613851342032Email miaomiaomyq@163.comIntroduction: Immunonutritional status is associated with the survival of DLBCL. This multicenter retrospective study aimed to explore the prognostic value of Prognostic Nutrition Index (PNI) in DLBCL patients by using propensity score matched analysis (PSM).Methods: A total of 990 DLBCL cases were recruited from 5 centers of Huaihai Lymphoma Working Group (HHLWG). A 1:1 PSM analysis was performed using the nearest-neighbor method, with a caliper size of 0.02. Cox regression analysis was used to examine factors associated with survival.Results: The median age at diagnosis was 62 years and 52.5% were males, with the 3-y overall survival of 65.1%. According to the MaxStat analysis, 44 was the optimal cut-off point of PNI. After PSM analysis, a total of 282 patients in PNI < 44 group could be propensity matched to PNI ≥ 44 patients, creating a group of 564 patients. Multivariable analysis revealed that PNI, age, central nervous system involvement and International Prognostic Index (IPI) were independent prognostic factors for DLBCL. Kaplan-Meier analysis indicated that patients with low PNI in Ann Arbor Stage (III/VI), ECOG (< 2), IPI (LR+LIR), GCB, and BCL-2 negative groups had a poor prognosis.Discussion: PNI could accurately stratify the prognosis of DLBCL after PSM analysis.Keywords: diffuse large B-cell lymphoma, prognostic nutrition index, propensity score matched, prognosis